Cool roof coating effect on the superficial temperature of rooftops in a warm and humid weather - Porras-Salazar, José Alí (2019)
Studies conducted in the field and in a laboratory show that cold roof coatings contribute to reduce heat transferability that occur through the roofs, which are one of the main causes of thermal discomfort in hot and humid climates. However, there is not enough research to quantify its benefits in tropical climates, and it lacks technical precision in many advertising material of the products available in the market. Therefore, in order to reduce this knowledge gap, this study analyzed the thermal behavior of galvanized iron sheets with zinc before and after applying a cold coating in the field. The surface temperature of the material was used as an indicator. During the two months that the experiment lasted, 95 observations were made at different times of the day where the surface temperature of the sheet with and without coating was measured, and the time and cloudiness of the sky were recorded. The results show that the sheet, in which the coating was applied, has a lower average temperature of 0.85 °C. This difference is statistically significant (p = 0.037) and is independent of the time of day and the cloudiness of the sky. However, the temperature differential is lower than previous studies found.